Systematic Literature Review (SLR): Peran Pancasila Dalam Membangun Keutuhan Bangsa Pasca Revolusi Indonesia - Syabania, Della Septiana; Usiono Usiono (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
The Fourth Industrial Revolution is currently upon us, thanks to globalization. People's thoughts, lifestyles, and interpersonal relationships are radically shifting because of the Revolution in Industrialization. Using the Internet of Things to apply the third wave of scientific and technological advancements is one of the innovations of the Fourth Industrial Revolution. Soon, the Smart shopping, smart homes, smart cities, and smart gadgets will all become commonplace, luring consumers to coexist peacefully. Indonesian nationals can utilize easy methods to stay up to date with the swift progress of technology. To entice individuals to come back and realize that Pancasila is the ethos for an independent and advanced Indonesia, It is envisaged that the Pancasila ideology will enable a region home to people with diverse social, economic, and physical disabilities to become developed and home to people whose standard of living is equivalent to or greater than that of other Indonesian communities. Research utilizing methods for gathering data from libraries, or studies whose research objects are analyzed through scientific journals, is what is known as literature review research. The first principle calls for the incorporation of Pancasila values into religious institutions while honoring variations in embraced beliefs or points of view. The value of humanity is the subject of the second transformation principle, which gives priority to an individual's inalienable human rights. In addition, the third transformation principle is applied towards national unity and integrity, making all Indonesian people work together to develop the industrial revolution 4.0 by making cultural adaptations. In addition, the fifth principle demands that everyone is treated equally and justice is sought for all Indonesians. This transformation can happen if everyone works together at all levels to make Pancasila the basis of industrial civilization. The Indonesian government and society will be strategically impacted by changes to Pancasila. Changes to Pancasila customs are intended to raise awareness Pancasila as a lifestyle that the founding fathers left behind. Pancasila should therefore be accepted as a prerequisite for working on national issues in a variety of domains, including social, economic, legal, and scientific and technological.. As a result, Indonesia will continue to hold fast to the values of Pancasila while modernizing.